Pengaruh Experiental Marketing dan Emotional Branding Terhadap Kepuasan Konsumen Mie Gacoan Malang - Rojil Gufron Abdilhaq; N. Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis aim of study are to portray effect of experiential marketing and emotional branding partially on consumer satisfaction in Mie Gacoan Malang. To determine the effect of experiential marketing and emotional branding simultaneously on consumer satisfaction of Mie Gacoan Malang. The population of this research is Malang Gacoan Noodle Consumers, amounting to 2,800 while the sample in this study is 100 consumers. Data analysis uses multiple linear regression analysis.The results showed that experiential marketing and emotional branding partially had a significant effect on consumer satisfaction in Mie Gacoan Malang. experiential marketing and emotional branding simultaneously have a significant effect on consumer satisfaction in Mie Gacoan Malang.Keywords: experiential marketing, emotional branding, customer satisfaction